2013
DOI: 10.1039/c2cc36839k
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent probe for rapid detection of thiols and imaging of thiols reducing repair and H2O2oxidative stress cycles in living cells

Abstract: A diselenide containing fluorescent probe based on a fluorescein scaffold for thiols was developed. The fluorescent probe exhibited rapid response, high selectivity and reversibility. Confocal fluorescence microscopy was used to visualize the redox changes mediated by thiols and reactive oxygen species in living HeLa cells.Intracellular thiols play an essential role in maintaining redox homeostasis by regulating the redox status between reduced free thiols and oxidized disulfides.1 Glutathione (GSH), which has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 36 publications
(31 reference statements)
1
56
0
3
Order By: Relevance
“…11 Until now, even though several fluorescent probes for HOCl 12 have been reported, few reversible fluorescent probes for visualizing the redox changes mediated by HOCl and antioxidants have been developed. 13 Here we present such a reversible fluorescent probe for HOCl.…”
mentioning
confidence: 99%
“…11 Until now, even though several fluorescent probes for HOCl 12 have been reported, few reversible fluorescent probes for visualizing the redox changes mediated by HOCl and antioxidants have been developed. 13 Here we present such a reversible fluorescent probe for HOCl.…”
mentioning
confidence: 99%
“…The results revealed that probe DPCA was able to be applied to complicated conditions with negligible interference from these species ( Figure S4). DPCA displayed good selectivity toward Cys, which outweighs numerous reported probes [60][61][62].…”
Section: Measurement Studies Of Probe Dpcamentioning
confidence: 71%
“…Finally, condensation of S1 and 2-benzothiazoleacetonitrile in the presence of piperidine provided probe 1 with the yield of 80%. [38,39]. These results suggest that probe 1 holds the big potential for real-time detection of ONOO  in biological systems.…”
Section: Synthesis Of Probementioning
confidence: 82%